"They're the Ones Who Hold the Answers": Exploring Educators' and Students' Conceptions of Academic Conversation. Issue 4 (15th December 2020) - Meston, Heather M.; Phillips Galloway, Emily; McClain, Janna Brown
Abstract: Purposeful academic conversation engages students as active agents in the process of making meaning from text, negotiating perspectives, and achieving mutual understanding. However, educators often report difficulties in engaging students in talk‐based pedagogies. This concern can be partially addressed by ensuring that students and teachers have similar understandings regarding the purposes of academic conversation. Here, we examine the conceptions of academic conversation held by middle‐school students and their teachers, revealing areas of convergence and divergence in the perspectives held by youth and their educators regarding the purposes of academic conversation and students' roles in these discussions. With direct relevance to instructional practice, we provide suggestions for making these understandings visible and reconciling divergent views.